Learner Motivation As A Moving Target: A Six-Month Study In A Rural English Course - Muhammad Akhyar; Irmayani; Anita Dwi Hapsari (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This study investigates how motivation can evolve over time within a fee-based private English course in East Java, Indonesia. Most existing studies have focused on formal educational contexts, and we investigate the realities of what can happen when participation is completely voluntary, meaning learners can actively disengage from learning at any time. This was carried out using Dörnyei's L2 Motivational Self System and Self-Determination Theory frame for motivation, following 18 students aged between 9 to 15 over a period of six months. Data were gathered via reflective journals & semi-structured interviews. The study found motivation in this context was not static, with motivation varying according to how students perceive the class atmosphere, teacher behavior, activities and their own feelings of progression. While many students were influenced by their parents to sign up for the course, they continued to attend feeling that they were being supported and they could do it. Little moments when they received something as simple as praise or were able to successfully complete something had an impact on their motivation and as such, the little praise was not insignificant. If learners encountered a situation where a task felt too difficult, or they did not receive feedback, motivation was lost which sometimes meant they stopped attending. Younger learners appeared to be more affected by if the class felt enjoyable, as older learners began to care about their future aspirations more. The study concludes that in non-formal English education, emotional security and meaningful teacher-student relationships are more crucial than rigid curricula or disciplinary structures.